Chronic lymphocytic leukemia with isochromosome 17q: An aggressive subgroup associated with TP53 mutations and complex karyotypes. (28th November 2017) - Collado, Rosa; Puiggros, Anna; López-Guerrero, José Antonio; Calasanz, M José; Larráyoz, M José; Ivars, David; García-Casado, Zaida; Abella, Eugènia; Orero, M Teresa; Talavera, Elisabet; Oliveira, Ana Carla; Hernández-Rivas, Jesús M; et al.
Abstract: Although i(17q) [i(17q)] is frequently detected in hematological malignancies, few studies have assessed its clinical role in chronic lymphocytic leukemia (CLL). We recruited a cohort of 22 CLL patients with i(17q) and described their biological characteristics, mutational status of the genes TP53 and IGHV and genomic complexity. Furthermore, we analyzed the impact of the type of cytogenetic anomaly bearing the TP53 defect on the outcome of CLL patients and compared the progression-free survival (PFS) and overall survival (OS) of i(17q) cases with those of a group of 38 CLL patients harboring other 17p aberrations. We detected IGHV somatic hypermutation in all assessed patients, and TP53 mutations were observed in 71.4% of the cases. Patients with i(17q) were more commonly associated with complex karyotypes (CK) and tended to have a poorer OS than patients with other anomalies affecting 17p13 (median OS, 44 vs 120 months, P  = 0.084). Regarding chromosomal alterations, significant differences in the median OS were found among groups ( P  = 0.044). In conclusion, our findings provide new insights regarding i(17q) in CLL and show a subgroup with adverse prognostic features. Highlights: CLL with 17p13 abnormalities is a heterogeneous group even at the cytogenetic level. 62% of the cases with i(17q) were associated with complex karyotypes. TP53 mutations were detected at a high frequency among CLL patients with i(17q). The type of 17p cytogenetic anomaly influences the prognosis of CLL patients.